Physical Fruit Traits, Nutritional Composition, and Seed Oil Fatty Acids Profiling in the Main Date Palm (Phoenix dactylifera L.) Varieties Grown in Morocco. (14th October 2021) - Ibourki, Mohamed; Azouguigh, Fadma; Jadouali, Si Mohamed; Sakar, El Hassan; Bijla, Laila; Majourhat, Khalid; Gharby, Said; Laknifli, Abdelatif
Abstract : We investigated fruit physical traits and nutritional value in both seed and flesh in eight Moroccan date palm varieties. The greatest values of weight for whole fruit, flesh, seed, and flesh percentage were found in "Boufgous, " "Agondari, " and "Bouskri." These two later varieties displayed also their superiority with respect to proximate composition. For fruit flesh, proximate composition, energy value, and reducing capacity ranged as follows: proteins (1.60–3.53%), moisture (5.31–17.31%), ash (2.08–2.50%), lipids (0.32–1.09%), carbohydrates (76.69–90.18%), energy value (338.30–385.89 kcal/100 g), and reducing capacity (100.14–1607.12 mg GAE/100 g). Corresponding values in seeds were as follows: proteins (3.20–5.00%), moisture (1.42–4.14%), ash (1.14–1.50%), lipids (6.30–7.40%), carbohydrates (83.39–85.55%), energy value (417.06–429.51 kcal/100 g), and reducing capacity (1427.71–6843.84 mg GAE/100 g dry weight). Among all minerals (K, Ca, Mg, B, Fe, Cu, Mn, Na, and Zn) found in both fruit parts, K had the highest records for both flesh (12047 mg/kg) and seed (6127.6 mg/kg), followed by Mg and Ca. Seeds lipidic fraction was dominated by monounsaturated fatty acid C18 : 1 (47.5%), followed by saturated fatty acids mostly C12 : 0 (18.0%), C14 : 0 (10.5%), and C16 : 0 (10.6%) and finally polyunsaturated fatty acid C18 : 2 (8.8%). It could be concluded that investigated varieties presented a great importance from a nutritional point of view, and seeds could present important opportunities of valorization.